Micropropagation of curry leaf (Murraya koenigii L.) - MADHUSOODANAN, K MARY MATHEW, Y S RAO, K PRADIP KUMAR, SALLYKUTTY JOSEPH, R LAKSHMANAN, K J (Journal of Spices and Aromatic Crops, 1999)
Micropropagation of curry leaf (Murraya koenigii) was standardized using nodal segments from mature trees on Murashige and Skoog media supplemented with 6-benzylaminopurine, kinetin, =naphthaleneacetic acid and ind'Ole-3-butyric acid as growth regulators. A multiplication ratio of 1:3 was observed over a 5 week culture period on media with benzylaminopurine (1.0 mg l-1), kinetin (0.5 mgl-1) and naphthaleneacetic acid (0.1 mg l-1). The best response of 1-2 roots per shoot was obtained on medium containing naphthaleneacetic acid and indolebutyric acid (0.1 mgl-1 each).